Allergic Rhinitis in Oman and Malaysia: The Similarities and Differences - Mohamad, Irfan; Ramli, Ramiza (Oman Medical Specialty Board, 2015)
I read with great interest the paper on allergic rhinitis entitled “Allergic rhinitis and associated comorbidities: Prevalence in Oman with knowledge gaps in literature” published in the November issue of the Oman Medical Journal.1It is a great finding of such a common disease whereby 48% of the patients with non-infective rhinitis were diagnosed as allergic rhinitis, which constituted 7% prevalence of the adult population presenting with nasal symptoms to the center.1 However, these fairly high figures are often overlooked. In fact, the burden of the disease is increasing, with the increase of the prevalence globally.